Impact of a Multi-disciplinary C. difficile Action Team. (4th October 2017) - Heil, Emily; Sivasailam, Bharathi; Park, SoEun; Diaz, Jose; Von Rosenvinge, Erik; Claeys, Kimberly; Hopkins, Teri; Leekha, Surbhi
Abstract: Background: Clostridium difficile infection (CDI) is associated with increased length of hospital stay, morbidity, mortality, and cost of hospitalization. Early intervention by experts from multiple areas of practice such as gastroenterology (GI), infectious diseases (ID) and surgery can be essential to optimize care and increase utilization of novel treatment modalities such as fecal microbiota transplant (FMT) and minimally invasive, colon-preserving surgical management. Methods: A multi-disciplinary C. difficile action team (MD-CAT) was implemented at University of Maryland Medical Center (UMMC) in March 2016 to engage appropriate specialty consultants in the care of CDI patients. The MD-CAT reviews positive C. difficile tests at UMMC and provides guidance and suggestions to the primary team including optimal antibiotic treatment (for CDI and any concomitant infection), and consultant involvement including ID, surgery, and GI, when appropriate. Using retrospective chart review, CDI patient management and outcomes were compared before and after implementation of the MD-CAT. Differences in the time to consults and frequency of interventional treatment was compared using Chi-square or Wilcoxon Rank-sum test. Results: We compared 48 patients with CDI in the pre-intervention with 89 patients in the post-intervention period. Demographic and clinical characteristics of the groups were similar. MD-CAT intervention was associated with frequent (73%) modification or discontinuation of concomitant antibiotics. Median time to GI and ID consults was significantly shorter in the post group ( P = 0.007 and P = 0.004, respectively). Five of 89 (5.6%) of patients received FMT or colon-preserving surgical intervention in the post-intervention group compared with no patients in the pre-intervention group. There was no difference in 30-day all-cause mortality or CDI recurrence between groups. Conclusion: Early, multi-disciplinary action on patients with CDI increased the proportion of patients undergoing active specialty consultation and improved use of concomitant antibiotics. A larger sample size is needed to determine the effects of such a team on other clinical outcomes. Disclosures: All authors: No reported disclosures.